Vegetation och ljudmiljö - Henriksson, Josefin (SLU/Landscape Architecture (until 121231), 2011)
Landscape architecture is a visual profession, but other senses also affect our interpretation of a place. Sounds can give us a lot of information about an environment, and they are often perceived as positive. Despite this, research about outdoor sounds most often focus on the reduction of unwanted sounds – noise – but the absence of noise does not result in a good soundscape. To accomplish this, sounds we appreciate are needed. This paper aims to investigate how landscape architects can contribute to a good soundscape. Through literature studies in acoustics and landscape architecture, it is investigated how solutions involving vegetation can reduce noise and add appreciated sounds in urban environments. The vegetation does not only affect the soundscape, but also adds aesthetic values and possibilities for recreation. For sounds to be appreciated, they need to relate to the location. This means that the concept of the good soundscape may vary within the city. Some are good because they are tranquil, others because they inspire activity. Most people appreciate subtle sounds such as the rush of water and the song of birds. Because of this, the design of a good soundscape often depends on effective noise control. It is determined that landscape architects with the use of vegetation on city roof tops, walls and floors are able to reduce noise levels as well as create attractive soundscapes.